Racial and Ethnic Economic Inequality: The International Record - Darity, William; Nembhard, Jessica Gordon (American Economic Review, 2000)
International racial and ethnic economic inequality is examined. The international record shows disparity across nations and regions, between racial and ethnic groups within countries, and within groups in the same country. Subalternate racial and ethnic populations, whether in the majority or minority, suffer remarkably similar economic outcomes across the globe. Institutional racism and cultural discrimination affect subcultures and different classes in multiple ways. In every country, those who get the short stick continue to face poor prospects for economic inclusion and justice.